Environmental Sustainability in Cameroon: Implications for Human Rights - Edumebong Smith Naseri (Zien Journals, 2021)
Cameroon has a plethora of laws that seek to protect the environment. These laws are seen as an attempt by the country to enhance its attempts towards achieving sustainable development. This paper critically examines the legal protection of the right to a healthy environment on Cameroon, through an elaboration of the various laws that seek to ensure both substantive and procedural rights in the country. This paper begins by establishing a connection between human rights and the environment, as well the rights and obligations entailed in environmental rights. Human rights standards are chosen based on the UNDP human rights principles. The paper further examines and provides an understanding of the definition and idea of the right a healthy environment. The paper also critically examines the various laws that protect the right and finally provides a critique of the protection of the right to a healthy environment in Cameroon through the various substantive and procedural rights entailed by the laws.
Keywords: Cameroon; plethora; environment; development